2015
DOI: 10.1199/tab.0177
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cambium Development

Abstract: Secondary phloem and xylem tissues are produced through the activity of vascular cambium, the cylindrical secondary meristem which arises among the primary plant tissues. Most dicotyledonous species undergo secondary development, among them Arabidopsis. Despite its small size and herbaceous nature, Arabidopsis displays prominent secondary growth in several organs, including the root, hypocotyl and shoot. Together with the vast genetic resources and molecular research methods available for it, this has made Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 156 publications
1
114
0
5
Order By: Relevance
“…Evidence accumulated in the past few years suggests that the distinct distribution of these two hormones plays pivotal roles in tissue patterning (Chandler and Werr, 2015;Schaller et al, 2015). For instance, in the vascular tissue of Arabidopsis roots, a central localized xylem axis bisects the intervening procambium cells and thus forms a bisymmetric structure (Nieminen et al, 2015;De Rybel et al, 2016). Cytokinin signaling peaks in two bisymmetric procambial cell files, where it regulates the localization of PINFORMED (PIN) auxin efflux carriers and creates an auxin maximum in the adjacent xylem axis.…”
Section: Mutually Exclusive Distribution Pattern Of Cytokinin and Auxmentioning
confidence: 99%
“…Evidence accumulated in the past few years suggests that the distinct distribution of these two hormones plays pivotal roles in tissue patterning (Chandler and Werr, 2015;Schaller et al, 2015). For instance, in the vascular tissue of Arabidopsis roots, a central localized xylem axis bisects the intervening procambium cells and thus forms a bisymmetric structure (Nieminen et al, 2015;De Rybel et al, 2016). Cytokinin signaling peaks in two bisymmetric procambial cell files, where it regulates the localization of PINFORMED (PIN) auxin efflux carriers and creates an auxin maximum in the adjacent xylem axis.…”
Section: Mutually Exclusive Distribution Pattern Of Cytokinin and Auxmentioning
confidence: 99%
“…Recently Schuller et al (2014) found that brassinosteroid (BR) biosynthesis was up-regulated in enlarged cells and that mutations in the BR receptor (bri1-6) and treatment with BR biosynthesis inhibitors reduced gall formation. Given the importance BR and other hormones such as strigolactones in regulating cambial activity and their extensive interactions with auxin and cytokinin (Nieminen et al 2015) a detailed microscopic analysis of host and plasmodial development in plants with mutations in these signalling pathways is likely to be informative.…”
Section: The Regulation Of Host Ck Metabolism and Response In Developmentioning
confidence: 99%
“…Arabidopsis secondary growth has been observed to occur in root, hypocotyl and stem (Nieminen et al 2015). Moreover, a comparative analysis between Arabidopsis and poplar hypocotyls has demonstrated that the produced secondary xylem of both plant species exhibit striking similarities in terms of tissue organization, albeit…”
Section: Towards Deciphering the Role Of Auxin In Biotic Stress Respomentioning
confidence: 99%
“…After subsequent periclinal divisions (parallel to the axis/surface) of the procambium during the late globular stage, heart stage and torpedo stage, the mature embryo displays a radial vascular patter with the vascular tissue in the center (Miyashima et al 2013). These embryonic-derived provascular tissues will generate the vascular system in the primary root and hypocotyl, whereas the shoot apical tissue is derived from the SAM (Nieminen et al 2015). On the other hand, in the embryonic cotyledons only a procambial tissue is extended in an apical-basal axis and will generate the leave veins (De Rybel et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation